Receiver Operating Characteristic (ROC) Analysis - Elizabeth Anne Krupinski (EARLI, 2017)
Visual expertise covers a broad range of types of studies and methodologies. Many studies incorporate some measure(s) of observer performance or how well participants perform on a given task. Receiver Operating Characteristic (ROC) analysis is a method commonly used in signal detection tasks (i.e., those in which the observer must decide whether or not a target is present or absent; or must classify a given target as belonging to one category or another), especially those in the medical imaging literature. This frontline paper will review some of the core theoretical underpinnings of ROC analysis, provide an overview of how to conduct an ROC study, and discuss some of the key variants of ROC analysis and their applications.